Phase-modulated X-Ray Emission from Cepheids due to Pulsation-driven Shocks - Moschou, Sofia-Paraskevi; Vlahakis, Nektarios; Drake, Jeremy J.; Evans, Nancy Remage; Neilson, Hilding R.; Guzik, Joyce Ann; ZuHone, John (The Astrophysical Journal, 2020)
Cepheids are pulsating variable stars with a periodic chromospheric response at UV wavelengths close to their minimum radius phase. Recently, an X-ray variable signature was captured in observations during the maximum radius phase. This X-ray emission came as a surprise and is not understood. In this work, we use the modern astrophysical code PLUTO to investigate the effects of pulsations on Cepheid X-ray emission. We run a number of hydrodynamic numerical simulations with a variety of initial and boundary conditions in order to explore the capability of shocks to produce the observed phase-dependent X-ray behavior. Finally, we use the Simulated Observations of X-ray Sources (SOXS) package to create synthetic spectra for each simulation case and link our simulations to observables. We show that, for certain conditions, we can reproduce observed X-ray fluxes at phases 0.4-0.8 when the Cepheid is at maximum radius. Our results span a wide range of mass-loss rates, 2 × 10-13 M⊙ yr-1 to 3 × 10-8 M⊙ yr-1, and peak X-ray luminosities, 5 × 10-17 erg cm-2 s-1 to 1.4 × 10-12 erg cm-2 s-1. We conclude that Cepheids exhibit two-component emission with (a) shock waves being responsible for the phase-dependent variable emission (phases 0.2-0.6) and (b) a separate quiescent mechanism being the dominant emission mechanism for the remaining phases.
Keywords: 1261; 1307; 1584; 1603; 1621; 1966; 2086; 305; 368; 739; 909; Astrophysics - High Energy Astrophysical Phenomena; Astrophysics - Solar and Stellar Astrophysics; Delta Cepheid variable stars; High energy astrophysics; Late-type stars; Magnetohydrodynamical simulations; Plasma astrophysics; Pulsating variable stars; Shocks; Stellar atmospheres; Stellar coronae; Stellar flares; Stellar physics